PENGARUH WORD OF MOUTH (WOM) DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI KANTOR CHERY MEDAN - ginting, Ebenezer; Purba , Mohd. Nawi; Ara Auza (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The results of research originating from data processing show a positive relationship between the Word of Mouth (WOM) variables and promotions on purchasing decisions at Chery Medan. Partially, the influence of Word of Mouth (WOM) and Promotion on Purchasing Decisions at Chery Medan is 0.819 and 0.553 respectively. Simultaneously, the Word of Mouth (WOM) and Promotion variables on Purchasing Decisions at Chery Medan are 0.446. From the results of the analysis it was found that partially Word of Mouth (WOM) and Promotion on Purchasing Decisions at Chery Medan were 44.6% and 45.8% respectively. Simultaneously, the influence of Word of Mouth (WOM) and Promotion on Purchasing Decisions at Chery Medan is 88.3% and the remainder is influenced by other variables not proposed in this research.